Analisis Faktor yang Mempengaruhi Keputusan Perawat dalam Penanganan Pasien dengan Kondisi Syok di Unit Gawat Darurat di RSUD Prof. Dr. W.Z. Johannes Kupang - Banin, Servasius Ratu (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Nurses' clinical judgment is a vital aspect in the management of patients with shock in the Emergency Department (ED). Factors such as work experience, level of knowledge, workload, and availability of facilities and infrastructure can influence the speed and accuracy of nurses' decisions. Objective: To determine the factors influencing nurses' decisions in the management of patients with shock in the ED of Prof. Dr. W.Z. Johannes Kupang Regional General Hospital. Method: This was a descriptive analytical study using a cross-sectional approach. Data were collected on January 3, 2025, through questionnaires distributed to 35 ED nurses. Logistic regression was used to analyze the dominant factors. Results: The study showed that knowledge (p=0.002), work experience (p=0.015), and availability of facilities (p=0.031) significantly influenced nurses' decisions. Workload (p=0.087) and team support (p=0.112) were not significant. The dominant factor was knowledge level, with an odds ratio (OR) of 3.8. Conclusion: Knowledge level is the most influential factor in nurses' decision-making in the management of shock patients in the ER. Routine training and shock management simulations are recommended to improve nurses' clinical response.